Optical design of transparent metal grids for plasmonic absorption enhancement in ultrathin organic solar cells - Kim, Inho; Lee, Taek Seong; Jeong, Doo Seok; Lee, Wook Seong; Kim, Won Mok; Lee, Kyeong-Seok (OPTICAL SOC AMER, 2013)
Transparent metal grid combining with plasmonic absorption enhancement is a promising replacement to indium tin oxide thin films. We numerically demonstrate metal grids in one or two dimension lead to plasmonic absorption enhancements in ultrathin organic solar cells. In this paper, we study optical design of metal grids for plasmonic light trapping and identify different plasmonic modes of the surface plasmon polaritons excited at the interfaces of glass/metal grids, metal grids/active layers, and the localized surface plasmon resonance of the metal grids using numerical calculations. One dimension metal grids with the optimal design of a width and a period lead to the absorption enhancement in the ultrathin active layers of 20 nm thickness by a factor of 2.6 under transverse electric polarized light compared to the case without the metal grids. Similarly, two dimensional metal grids provide the absorption enhancement by a factor of 1.8 under randomly polarized light. (C) 2013 Optical Society of America